2004
DOI: 10.1203/01.pdr.0000113770.22794.df
|View full text |Cite
|
Sign up to set email alerts
|

Soluble Adhesion Molecules and Cytokines in Children Affected by Recurrent Infections of the Upper Respiratory Tract

Abstract: The objective of this study was to compare plasma levels of soluble adhesion molecules and Th1-Th2 type cytokines in 44 children with frequently recurrent respiratory infections (FRRI) of upper airways, defined as having nine or more episodes per year, and in 34 children without recurrence; all subjects were followed-up for 12 mo. The viral etiology was determined by cultures from nasal, pharyngeal, and ear secretions, using PCR and immunofluorescence. Plasma levels of five soluble adhesion molecules (E-select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 33 publications
0
5
1
Order By: Relevance
“…Thirdly, we cannot infer on the relative contribution of upper airway tissues such as tonsils and adenoids to the systemic cytokine levels (44), an issue that clearly merits further investigation. Finally, the levels of IL-10 found herein are somewhat lower than those previously reported (45,46). These differences may simply reflect slightly different methodologies in sample processing or in the assay itself.…”
Section: Discussioncontrasting
confidence: 83%
“…Thirdly, we cannot infer on the relative contribution of upper airway tissues such as tonsils and adenoids to the systemic cytokine levels (44), an issue that clearly merits further investigation. Finally, the levels of IL-10 found herein are somewhat lower than those previously reported (45,46). These differences may simply reflect slightly different methodologies in sample processing or in the assay itself.…”
Section: Discussioncontrasting
confidence: 83%
“…Increased levels of IFN-γ have also been shown to enhance macrophage function and secretion of IgG2a, thus propagating and sustaining immune modulating signals [22,23]. Reduced plasma levels of IFN-γ have been found in children with recurrent infections of the upper respiratory tract and in animals lacking the transcription factor T-bet, which are known to be highly susceptible to respiratory infections [11,12,24,25]. Release of these cytokines during a respiratory viral infection is also known to affect the duration of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…These cytokines are thought to comprise one of the principal host defense mechanisms against many intracellular pathogens including respiratory viruses [8][9][10]. Studies on children and adults, and CD4 −/− mouse models have demonstrated that an attenuated production of these cytokines relates with a diminished cell mediated immune response to respiratory virus, loss of cytolytic activity of CD8 + lymphocytes, reactivation of latent infection and consequently recurrence of respiratory viral infections [11][12][13]. In addition, in a study relating stress levels to the frequency of URIs, both low NK cell number and cytotoxicity of NK cells was found to be associated with increased risk of URIs [14].…”
Section: Introductionmentioning
confidence: 99%
“…Our findings could therefore be due to a bystander effect of an inflammatory microenvironment created by recurrent or persistent GABHS infection. Indeed, soluble adhesion molecules have been reported as persistently elevated in recurrent paediatric upper respiratory tract infections of viral origin [28], and the possibility of a subclinical GABHS pharyngeal carriage has been thoroughly documented [29]. However, if this was the case, one would expect adhesion molecule titers to correlate with ASOT or anti-DNAse B titers, both highly specific markers of an ongoing immune response to this agent.…”
Section: Discussionmentioning
confidence: 99%